2009
DOI: 10.14236/ewic/ease2009.1
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Support for Two Refactoring Studies Using Commercial C# Software

Abstract: This paper documents a study of the application of refactorings in commercial C# software comprising 270 versions over a two-month period. The software was developed in a continuous integration environment in a large, multinational company where each software change committed to the source control was regarded as a new version. The aim of the research was to compare and contrast the results from two previous refactoring studies with those of the C# software. Method. A tool was developed to compare each version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Results indicated that considering the dependencies among tests is key for deciding whether refactor a test code. Gatrell et al 32 investigated test refactorings over 270 versions of commercial C# software, and results indicated that base refactorings are common and complex structural refactorings are relatively rare. Bleser et al 33 performed two empirical studies to analyze the diffusion of test smells at class level of 164 open‐source SCALA projects and assess the developers' perception of test smells.…”
Section: Related Workmentioning
confidence: 99%
“…Results indicated that considering the dependencies among tests is key for deciding whether refactor a test code. Gatrell et al 32 investigated test refactorings over 270 versions of commercial C# software, and results indicated that base refactorings are common and complex structural refactorings are relatively rare. Bleser et al 33 performed two empirical studies to analyze the diffusion of test smells at class level of 164 open‐source SCALA projects and assess the developers' perception of test smells.…”
Section: Related Workmentioning
confidence: 99%
“…Gatrell, Counsell, and Hall [26] explored the difference between applying the refactoring in production classes and test classes. An empirical study presented to compare the findings from two prior refactoring studies by using versions anonymous commercial C# system from a large company.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there are need to conduct more studies on them to confirm the current results. Furthermore, six studies ([3], [13], [26], [28], [30], [37]) explored the influence of the refactoring on the quality attributes in general without identifying which internal or external attribute have improved. Furthermore, to the best of our knowledge, there is lack of studies that require to investigate the refactoring impact on the several external quality attributes such as adaptability, analyzability, comprehensibility, completeness, effectiveness, flexibility, security, and extendibility.…”
Section: • External Quality Attributesmentioning
confidence: 99%
“…Finally, there have been a few attempts to study code smells for the C# language [26], [27]. However, they lack both scale in terms of the number of projects they process and breadth of analysis in terms of the number of smells they examine.…”
Section: Related Workmentioning
confidence: 99%